Difference between revisions of "99 questions/Solutions/19"

From HaskellWiki
Jump to navigation Jump to search
(Remove solution that doesn't work)
 
(2 intermediate revisions by 2 users not shown)
Line 51: Line 51:
 
</haskell>
 
</haskell>
   
or calculate the position(index) at first:
+
or calculate the position at first:
   
 
<haskell>
 
<haskell>
Line 73: Line 73:
 
| otherwise = let (f,s) = splitAt n xs in s ++ f
 
| otherwise = let (f,s) = splitAt n xs in s ++ f
 
where len = length xs
 
where len = length xs
</haskell>
 
 
Without using <hask>length</hask>:
 
<haskell>
 
rotate xs n
 
| n > 0 = (reverse . take n . reverse $ xs) ++ (reverse . drop n . reverse $ xs)
 
| n <= 0 = (drop (negate n) xs) ++ (take (negate n) xs)
 
 
</haskell>
 
</haskell>
   
Line 92: Line 85:
 
</haskell>
 
</haskell>
   
  +
Here's another solution without using length. If the order of the arguments is reversed so that the integer comes before the list, then it is possible to define rotation by n as rotation by (n-1) followed by rotation by 1 recursively (with suitable modifications to support negative rotations). This leads to the following solution:
 
<haskell>
  +
rotate :: [a] -> Int -> [a]
 
rotate xs n = rot n xs
  +
where rot 0 = id
  +
rot 1 = \xs -> case xs of [] -> []; xs -> tail xs ++ [head xs]
  +
rot (-1) = \xs -> case xs of [] -> []; xs -> (last xs):init xs
  +
rot n
  +
| n > 0 = (rot (n-1)).(rot 1)
  +
| n < 0 = (rot (n+1)).(rot (-1))
 
</haskell>
   
 
[[Category:Programming exercise spoilers]]
 
[[Category:Programming exercise spoilers]]

Latest revision as of 20:35, 23 May 2021

(**) Rotate a list N places to the left.

Hint: Use the predefined functions length and (++).

rotate [] _ = []
rotate xs 0 = xs
rotate (x:xs) (n+1) = rotate (xs ++ [x]) n
rotate xs n = rotate xs (length xs + n)

(Note that this solution uses n+k-patterns which are removed from Haskell 2010.)

There are two separate cases:

  • If n > 0, move the first element to the end of the list n times.
  • If n < 0, convert the problem to the equivalent problem for n > 0 by adding the list's length to n.

or using cycle:

rotate xs n = take len . drop (n `mod` len) . cycle $ xs
    where len = length xs

or using list comprehension (only works for sequential increasing elements):

rotate :: (Enum a) => [a] -> Int -> [a]
rotate xs n = [(f n) .. last xs] ++ [head xs .. (f (n-1))]
              where f k = xs !! (k `mod` length xs)

or without mod:

rotate xs n = take (length xs) $ drop (length xs + n) $ cycle xs

or

rotate xs n = if n >= 0 then
                  drop n xs ++ take n xs
              else let l = ((length xs) + n) in
                  drop l xs ++ take l xs

or

rotate xs n | n >= 0 = drop n xs ++ take n xs
            | n < 0 = drop len xs ++ take len xs
                      where len = n+length xs

or calculate the position at first:

rotate xs n = let i = if n < 0 then length xs + n else n
              in drop i xs ++ take i xs

or

rotate xs n = drop nn xs ++ take nn xs
    where 
      nn = n `mod` length xs

Using a simple splitAt trick

rotate xs n
    | n < 0 = rotate xs (n+len)
    | n > len = rotate xs (n-len)
    | otherwise = let (f,s) = splitAt n xs in s ++ f
    where len = length xs

A much simpler solution without using length that is very similar to the first solution:

rotate :: [a] -> Int -> [a]
rotate [] _ = []
rotate x 0 = x
rotate x y
  | y > 0 = rotate (tail x ++ [head x]) (y-1)
  | otherwise = rotate (last x : init x) (y+1)

Here's another solution without using length. If the order of the arguments is reversed so that the integer comes before the list, then it is possible to define rotation by n as rotation by (n-1) followed by rotation by 1 recursively (with suitable modifications to support negative rotations). This leads to the following solution:

rotate :: [a] -> Int -> [a]
rotate xs n = rot n xs
    where rot 0 = id
          rot 1 = \xs -> case xs of [] -> []; xs -> tail xs ++ [head xs]
          rot (-1) = \xs -> case xs of [] -> []; xs -> (last xs):init xs
          rot n
              | n > 0 = (rot (n-1)).(rot 1)
              | n < 0 = (rot (n+1)).(rot (-1))